The influence of pump-turbine specific speed on hydraulic transient processes - Giljen, Zdravko (Strojniški vestnik, 2024)
The main porpose of this paper is to perform and present at transient process analysis on the influence of different specific speeds (nq) of the three-model pump-turbines that may implemented at the hydropower pump storage plant (HPSP) Bajina Basta, Serbia. The intention is to analyze the operation regimes along the S-shaped characteristic curve, which creates difficulties in calculations during the load-rejection process. These problems are manifested by an unusual increase in water pressure, followed by an increase in machine vibrations, thus threatening the stability of machine operation. The subject of this research is the four-quadrant (4Q) characteristic curves, presented in the form of Suter curves (the head and momentum parameters (Wh and Wm), in dependence of angle (?)) for different wicket gate openings, of the three pump-turbine models with different specific speeds (nq = 27, nq = 38 and nq = 50). These 4Q characteristics are used as input data for numerical code developed to calculate the simultaneous load rejection of both pump-turbines. The numerical code is based on the method of characteristics and applied to the test case at HPSP. This is especially relevant when dealing with characteristic S-shaped curves that may lead to serious instability in operation during the transient process. The calculation results show changes in the pressure, speed of rotation and discharge of the machine operation regimes, but the important findings are reflected in further application of the results to determine the parametric flow and speed (Q11 and n11) trajectories of the operating points, where the unstable behavior of a pump-turbine operating in turbine mode is presented and periodically the trajectories also pass through the reverse pump zone.
Keywords: črpalne turbine; hidravlični prehodni pojavi; hydraulic transients; influence of the specific speed; load rejection; method of characteristics; metoda karakteristik; pump turbines; razbremenitev; trajektorija delovne točke; vpliv specifične hitrosti; working point trajectory